Toxicity and Prevailing factors on Thyroid gland and its Herbal Treatment – A review (Journal of Pharmaceutical Negative Results, 2022)
The human body is one of the very apt examples to understand that many systems have to work in rhythm and coherence in order for overall functioning, including systems that work together like the cardiac system, respiratory system, renal system, nervous system, digestive system, endocrine system, and many more. Regard to each system plays many specific and magnificent roles in the body and helps in the sustenance of life. This paper throws light on the specificity of the endocrine system and enables many facts of roles in the human body, governing vital functions through its governing functions as well as its prevailing factors leading to toxicity, also discussing its herbal remedies for the malfunctions caused due to this system. They could be many perfectors to these conditions like toxicity, lifestyle patterns, medications, comorbid factors, and many more. Toxicity could be of various reasons which would affect the various biological synthesis of the human body. The hormonal balance that needs enzymes and chemical compounds to support its normal cycle would interfere with the chemicals, metals etc that are present in the environment and causes toxic agents which would disrupt the normal synthesis, thus leading to various disabilities, ailments, and disorders etc. It is thereby discussed through the correlation of multiple reviews that when there is a lack of stasis in the system, could disrupt the ability of the body to adapt to multiple bodily outcomes. Thyroid disorder is one of the major prevailing conditions due to the misfunctioning of the endocrine system.